If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + 2w = 11 Solving 3u + 2w = 11 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2w' to each side of the equation. 3u + 2w + -2w = 11 + -2w Combine like terms: 2w + -2w = 0 3u + 0 = 11 + -2w 3u = 11 + -2w Divide each side by '3'. u = 3.666666667 + -0.6666666667w Simplifying u = 3.666666667 + -0.6666666667w
| 7-3a=-2(-7+2a) | | 3n-5+6n-17=167 | | 2(1+7r)+5r=2+7r | | x^2=-24x | | -2-4a=6-a-3a | | -2-4a=6-a | | 6-7x=-7+6 | | (x-y)(x^2-7xy+y^2)=0 | | 30x+2=902 | | 31=-8(3n-2)-3(4+n) | | (3v^4+6v)-5v^4-4v+8= | | -6=-4x+7x | | (6x+11)*log(4)=(x-1)*log(16) | | 103=8(7-m)+7 | | 4n+42+n-100=2942 | | 103=8(3n-2)-3(4+n) | | 4z=1.7+4.3 | | x^2-3*x=22 | | x^2-3*tan(4*3x)=12 | | 5+3a+3=23 | | 0.8p=-112 | | x+9-2sqrtx+24=0 | | log(5x+7)=1+log(x-6) | | 7y=6(y+6) | | 3x-4x=65 | | 5(2+3x)-1=-6 | | (x+3y)(5x+3y)= | | (4y+2)(4-y)=0 | | 2z=1.8+0.8 | | 56=14y-7y | | (3y^2-5y+2)-(3y^6)=19 | | -0.4x=-12 |